Some Local Contour-Solid Theorems for Finely Holomorphic Functions - Sarana, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We prove some local contour-solid theorems for finely holomorphic functions defined on sets of the complex plane that are finely open with nonpolar complements.